La Independencia del Indecopi en tiempos de crisis: a propósito del riesgo de la presión política en la agencia de competencia peruana - Sandoval Valer, Jeysson (2020)
The independence of competition agencies is vital to guarantee that they operate in an objective and technical manner. Multiple papers have been written about the importance of stablishing a solid institutional framework that protects these entities from foreign influences, referring mostly to pressure from economic actors. However, they are not the only ones interested in interfering with the decisions made by competition agencies, political actors are too. In this article, the authors evaluate the institutional framework of Indecopi, the Peruvian competition agency, and determine whether or not it guarantees the institution’s independence against political pressures. For this, they utilize historical, comparative and case based analysis. Additionally, the authors evidence how crisis situations increase the risks associated with a lack of independence. Finally, they propose possible solutions that can be employed to reduce said risks.